2021
DOI: 10.3171/2020.7.jns192210
|View full text |Cite
|
Sign up to set email alerts
|

Internal dose escalation associated with increased local control for melanoma brain metastases treated with stereotactic radiosurgery

Abstract: OBJECTIVE The internal high-dose volume varies widely for a given prescribed dose during stereotactic radiosurgery (SRS) to treat brain metastases (BMs). This may be altered during treatment planning, and the authors have previously shown that this improves local control (LC) for non–small cell lung cancer BMs without increasing toxicity. Here, they seek to identify potentially actionable dosimetric predictors of LC after SRS for melanoma BM. METHODS The records of patients with unresected melanoma BM treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…When the prescribed dose is 30 Gy/3 fractions (the median dose in this study) in an 80% isodose, achieving GTV D80 > BED20 58 is difficult; an inhomogeneous dose distribution is required. In previous studies, inhomogeneous dose distribution correlated with good local control after Gamma Knife radiotherapy 20 , 21 and resulted in better local control than did homogeneous distribution after Linac‐based SRT. 22 BED20 58 is approximately 41.5 Gy/5 fractions and is similar to BED10 80.…”
Section: Discussionmentioning
confidence: 80%
“…When the prescribed dose is 30 Gy/3 fractions (the median dose in this study) in an 80% isodose, achieving GTV D80 > BED20 58 is difficult; an inhomogeneous dose distribution is required. In previous studies, inhomogeneous dose distribution correlated with good local control after Gamma Knife radiotherapy 20 , 21 and resulted in better local control than did homogeneous distribution after Linac‐based SRT. 22 BED20 58 is approximately 41.5 Gy/5 fractions and is similar to BED10 80.…”
Section: Discussionmentioning
confidence: 80%
“…Although generally unregarded dose attenuation margin outside the prescription IDS can cover these uncertainties to some degree, an approximately 1-mm setup error likely leads to marginal tumor residues, given the generally steep dose gradient for LGK [5]. Meanwhile, recent studies also suggest that the higher proportion of GTV receiving ≥30-32 Gy in the single fraction, i.e., internal dose escalation, is likely associated with superior tumor shrinkage and LC [8,9,19]. In LGK, 50% IDS is generally used for target coverage and dose prescription in multi-shot planning, i.e., a combination of multi-isocenter, which can lead to superior tumor response, particularly if concentrically laminated steep dose increase inside the GTV boundary is achieved [5,11].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a steep dose increase inside the GTV boundary, i.e., an extremely inhomogeneous GTV dose can also be beneficial to enhance anti-BM efficacy by conquering the potential internal radioresistant portion and is also deemed as another essential integrant for suitable dose distribution [5,7]. Several studies suggest the advantage of so-called internal dose escalation for effecting superior tumor shrinkage and LC [8,9]. Thus, in addition to the prescribed marginal dose, the appropriateness of the dose gradient both outside and inside the GTV boundary is an indispensable requisite for SRS planning for BM [5].…”
Section: Introductionmentioning
confidence: 99%
“…Vogelbaum et al reported an increased risk of local failure for brain metastases treated with 15 Gy and 18 Gy compared to 24 Gy, with a one-year LC of 45%, 49% and 85%, while higher prescription dose exhibited significantly longer time to local failure (p = 0.0005) [21]. Furthermore, other studies also noticed that doses in excess of prescription dose were predictive of LC [22,23].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 97%